Temporal and spatial coordination of DNA segregation and cell division in an archaeon - Joe Parham; Valerio Sorichetti; Alice Cezanne; Sherman Foo; Yin-Wei Kuo; Baukje Hoogenberg; Arthur Radoux-Mergault; Eloise Mawdesley; Lydia Daniels Gatward; Jerome Boulanger; Ulrike Schulze; Anđela Šarić; et al. (Proceedings of the National Academy of Sciences, 2025)
Cells must coordinate DNA segregation with cytokinesis to ensure that each daughter cell inherits a complete genome. Here, we explore how DNA segregation and division are mechanistically coupled in archaeal relatives of eukaryotes, which lack Cyclin-dependent kinase (CDK)/Cyclins. Using live cell imaging, we first describe the series of sequential changes in DNA organization that accompany cell division in Sulfolobus, which computational modeling shows likely aid genome segregation. Through a perturbation analysis we identify a regulatory checkpoint which ensures that the compaction of the genome into two spatially segregated nucleoids only occurs once cells have assembled a division ring—which also defines the axis of DNA segregation. Finally, we show that DNA compaction and segregation depend, in part, on a ParA homologue, SegA, and its partner SegB, whose absence leads to bridging DNA. Taken together, these data show how regulatory checkpoints like those operating in eukaryotes aid high-fidelity division in an archaeon.